قابلية البيئة القانونية للسياحة الحلال في ليبيا - Ahmad, Abdulbari Mabruk Elfituari; Negasi, Mohamed Ibrahim; Laeba, Muhammad (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2019)
Tourism is an important component of social and economic development . It is a means of communication between peoples and their cultures, as well as a means of self - recreation and refinement, especially if the tourist destination is for religious reasons. There is no doubt that the economic importance of tourism activity and its role in achieving large financial resources in many countries, Which has the potential of natural or cultural tourism, given some of the privacy that characterizes the Muslim tourist, which requires tourism services in line with Islamic law, emerged in the last decade phenomenon of tourism Halal, which are in line with Islamic law and provide the conditions for These requirements require most countries interested in the tourism sector to establish a legal in frastructure suitable to attract those interested in Halal tourism. This interest calls on the researcher to explore and uncover this phenomenon in Libya through exploration and searching for laws and regulations that regulate tourism or provide conditions And the findings of this research show that the concept of Halal tourism has legal bases in Libya derives its legitimacy from the Islamic Sharia, but these legal texts are distributed between different legislation, and some need to further clarification and scrutiny through the And the interest in the phenomenon of Halal tourism in Libya requires more explicit legal provisions in the Libyan Tourism Law to keep up with the global phenomenon and be a source of attraction for those wishing to tourism according to Islamic rules.